Family waqf as progressive technique for poverty extermination: a headlong for human development in southern region of Nigeria - Salman, mailto:salmanjamiu2iium@gmail.com; Sadique, Muhammad Abdurrahman; Mohamad, Nor Asiah; Halim, Akmal Hidayah (Albukhary International University, 2021)
The objectives of the current study are in three folded: i) to determine the needs for family waqf emergent as a resolution to endemic poverty ii) to explore how could family waqf would contribute to the human development for the purpose of alleviating poverty and iii) to provide recommendations of family waqf as headlong for human Development in Southern Region of Nigeria. Since the study is purely exploratory hence; it carried out document analysis as it affected the human development. Through the findings, it has been established that there is an urgent need to streamline the legal framework for waqf in Nigeria through proper legislation. The proposed legislation on waqf should only contain general guidelines for the regulation and management of waqf properties and waqf-related issues in the country. The economic potentials of such awqāf property is beyond doubt which would solve the poverty paralyses among the less privilege and poor. The foregoing finding is not exhaustive and is only intended to serve as a launching pad for further research in this area